Nirmal Sengupta. Managing Common Property. Irrigation in India and the Philippines. Nueva Delhi/Newbury Park/ Londres: Sage, 1991, 283 pp. (Indo-dutch studies on develpment alternatives-6) (cuadros, diagramas y mapas). - Devalle, Susana B. C. (Estudios de Asia y África, 1992)
-